2017
DOI: 10.1111/nmo.13162
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between 5‐HT4 receptor stimulation and phosphodiesterase 4 inhibition in facilitating acetylcholine release in human large intestinal circular muscle

Abstract: In human large intestinal circular muscle, the intracellular pathway of 5-HT receptors facilitating cholinergic neurotransmission to large intestinal circular smooth muscle is controlled by PDE4. If the synergy between 5-HT receptor agonism and PDE4 inhibition is confirmed in a functional assay with electrically induced cholinergic contractions of human large intestinal circular smooth muscle strips, combination of a selective 5-HT receptor agonist with a selective PDE4 inhibitor might enhance the in vivo prok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
0
6
1
Order By: Relevance
“…But obviously, in C57Bl/6J murine GI circular muscle, neither cilostamide nor rolipram allows to obtain more pronounced electrically induced cholinergic contractions with prucalopride. This contrasts to the situation in porcine stomach and colon, and human large intestine where the PDE4 inhibitors rolipram and roflumilast enhance the effect of prucalopride on electrically induced cholinergic contractions and/or acetylcholine release ( Priem et al, 2012 , 2013 ; Lefebvre et al, 2016 ; Pauwelyn et al, 2018 ) and points to important species differences. It cannot be excluded that the investigation of other mouse strains might lead to different results.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…But obviously, in C57Bl/6J murine GI circular muscle, neither cilostamide nor rolipram allows to obtain more pronounced electrically induced cholinergic contractions with prucalopride. This contrasts to the situation in porcine stomach and colon, and human large intestine where the PDE4 inhibitors rolipram and roflumilast enhance the effect of prucalopride on electrically induced cholinergic contractions and/or acetylcholine release ( Priem et al, 2012 , 2013 ; Lefebvre et al, 2016 ; Pauwelyn et al, 2018 ) and points to important species differences. It cannot be excluded that the investigation of other mouse strains might lead to different results.…”
Section: Discussioncontrasting
confidence: 58%
“…It would be optimal to study the influence of PDE inhibition on basal and 5-HT 4 receptor-stimulated acetylcholine release by measuring acetylcholine release directly. But a set of preliminary experiments showed that our method, applied to measure tritiated acetylcholine release in porcine and human GI tissue ( Lefebvre et al, 2016 ; Pauwelyn et al, 2018 ), was not able to pick up consistent values in murine GI tissues. When studying then the influence of PDE inhibitors in a functional model where electrically induced cholinergic muscle contractions are enhanced with a 5-HT 4 receptor agonist, one has to take in account their possible influence at the muscular level.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Specifically, PDE4D may mediate this effect upon PDE4 inhibition, as PDE4D has been found to be recruited to CFTR via binding the scaffolding protein Shank2 (Lee et al, 2007). Moreover, PDE4 inhibition can facilitate 5HT4 receptor-mediated acetylcholine release, causing contraction of large intestinal circular smooth muscle (Pauwelyn et al, 2018). Specifically, the PDE4D3 and PDE4D5 isoforms have been found to associate with 5HT4(b) receptors and may, therefore, be involved in gastrointestinal effects caused by PDE4(D) inhibition (Weninger et al, 2014).…”
Section: B Dizzinessmentioning
confidence: 99%